Beginning Java Data Structures and Algorithms - James Cutajar (Packt Publishing, 2018)
This book, "Beginning Java Data Structures and Algorithms", introduces you to the critical concepts of algorithms and data structures using Java. Through practical examples and activities, you will gain the skills to design, analyze, and implement efficient programs.What this Book will help me doMaster the use of basic and composite data structures like lists, trees, and graphs.Understand and apply sorting algorithms such as QuickSort and MergeSort.Gain a firm grasp of algorithmic analysis and Big O notation.Learn algorithm design paradigms such as dynamic programming and greedy algorithms.Develop efficient solutions to complex problems using graph theory and string matching approaches.Author(s)James Cutajar is an experienced software developer and technical educator with a passion for teaching programming concepts effectively. He has written several educational resources on Java and algorithms, helping thousands of students improve their understanding. His clear explanations and relatable examples make complex topics approachable.Who is it for?This book is for aspiring and intermediate Java developers who seek to strengthen their knowledge in algorithms and data structures to improve their coding efficiency and problem-solving abilities. It is also suitable for students studying computer science topics who want hands-on examples in Java, as well as professionals looking to brush up on these important programming skills in a practical and applicable way.